Obstacles to Strategic Planning at the Higher Institute for Teacher Training in Abéché, Chad (The International Journal of Educational Sciences and Arts, 2026)
This study investigated the obstacles to strategic planning at the Higher Institute for Teacher Training in Abéché, Chad. A descriptive-analytical research design was employed, and data were collected from a randomly selected sample of 56 participants using a structured questionnaire. Secondary data were obtained from relevant literature and documentary sources. The data were analysed using the Statistical Package for the Social Sciences (SPSS), applying descriptive statistical techniques, including frequencies, percentages, means, and standard deviations.The findings indicate that all identified obstacles to strategic planning exerted a moderate level of influence, with an overall mean score of 2.32. Technical obstacles emerged as the most significant, particularly the limited capacity to use modern technologies and equipment and the inability to keep pace with contemporary developments required for effective strategic planning. Human resource obstacles ranked second and included a shortage of qualified personnel to implement strategic plans and the limited involvement of teachers in the strategic planning process. Administrative obstacles were reflected in the prioritization of short-term operational objectives over long-term strategic goals. Organizational obstacles ranked last and were associated with the failure to prioritize strategic planning as an institutional function and the limited participation of different administrative units in the development of strategic plans.
Keywords: Obstacles; Strategic Planning; Higher Institute; Teacher Preparation; Abéché